2012
DOI: 10.1242/jcs.115220
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione peroxidase 3, a new retinoid target gene, is crucial for human skeletal muscle precursor cell survival

Abstract: SummaryProtection of satellite cells from cytotoxic damages is crucial to ensure efficient adult skeletal muscle regeneration and to improve therapeutic efficacy of cell transplantation in degenerative skeletal muscle diseases. It is therefore important to identify and characterize molecules and their target genes that control the viability of muscle stem cells. Recently, we demonstrated that high aldehyde dehydrogenase activity is associated with increased viability of human myoblasts. In addition to its deto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 58 publications
(68 reference statements)
2
56
0
1
Order By: Relevance
“…This result is consistent with previous studies, which found spironolactone prevents aldosterone‐induced inflammation and oxidative stress in cardiac cells; the authors speculated that it may be able to prevent oxidative stress that contributes to cardiac muscle wasting (40, 41). A previous study found that cells under oxidative stress up‐regulate the alcohol dehydrogenases ADH1B and ADH1C in order to convert retinol to retinoic acid, which has been shown to protect muscle cells (42). Retinoic acid in turn up‐regulates glutathione peroxidase GPX3 , which is a regulator of its antioxidant effects.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with previous studies, which found spironolactone prevents aldosterone‐induced inflammation and oxidative stress in cardiac cells; the authors speculated that it may be able to prevent oxidative stress that contributes to cardiac muscle wasting (40, 41). A previous study found that cells under oxidative stress up‐regulate the alcohol dehydrogenases ADH1B and ADH1C in order to convert retinol to retinoic acid, which has been shown to protect muscle cells (42). Retinoic acid in turn up‐regulates glutathione peroxidase GPX3 , which is a regulator of its antioxidant effects.…”
Section: Discussionmentioning
confidence: 99%
“…As there are data to suggest that at least in old Wistar rats, hypertrophy would be expected to precede nuclear acquisition (van der Meer et al, 2011a), the importance of oxidative stress to negatively affect differentiation of activated satellite cells and muscle regeneration (El et al, 2012) and thereby limit the ability to add new nuclei to the reloaded muscles as a mechanism to enhance hypertrophy (Wust et al, 2007) and improve recovery from muscle wasting requires additional investigation.…”
Section: Discussionmentioning
confidence: 99%
“…El Haddad et al [77] reported that healthy and FSHD muscles pretreated with retinoic acid (RA; a metabolite of vitamin A) presented lower ROS levels and apoptosis than when exposed to H 2 O 2 overnight (both P < 0.05). Additionally, myoblast adhesion was restored by pretreatment with RA and associated with a higher IC50 (the H 2 O 2 concentration at which half of the cells adhere to the culture dish).…”
Section: Antioxidants and Fshdmentioning
confidence: 99%